2019
DOI: 10.1038/s41598-019-41472-y
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA-449 family mediates doxorubicin resistance in triple-negative breast cancer by regulating cell cycle factors

Abstract: The mechanisms of chemotherapy resistance in triple negative breast cancer remain unclear, and so, new molecules which might mediate this resistance could optimize treatment response. Here we analyzed the involvement of the miRNA-449 family in the response to doxorubicin. The cell viability, cell-cycle phases, and the expression of in silico target genes and proteins of sensitive/resistant triple negative breast cancer cell lines were evaluated in response to doxorubicin treatment and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…miRNA-143-3p increase the sensitivity of TNBC to paclitaxel by inferenig with CIAPIN1 expression, a cytokineinduced apoptosis inhibitor 1 protein [161]. miR-449 can induce doxorubicin respone in TNBC by downregulating cell cycle related genes [162]. Such combinations, which are already tested in BC preclinical models have the potential to be tested for BCBM.…”
Section: Mirna and Bcbm Therapeuticsmentioning
confidence: 99%
“…miRNA-143-3p increase the sensitivity of TNBC to paclitaxel by inferenig with CIAPIN1 expression, a cytokineinduced apoptosis inhibitor 1 protein [161]. miR-449 can induce doxorubicin respone in TNBC by downregulating cell cycle related genes [162]. Such combinations, which are already tested in BC preclinical models have the potential to be tested for BCBM.…”
Section: Mirna and Bcbm Therapeuticsmentioning
confidence: 99%
“…In China, incidence rate is growing at more than twice the rate of global growth, especially in urban areas [4]. Triple negative breast cancer (TNBC) is a subtype of breast cancer which lack of estrogen receptor, progesterone receptor and low expression of human epidermal growth factor receptor 2 (HER 2) [7][8][9]. Due to these, the prognosis was worse than other subtypes of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Tormo et al showed that miR-449 affects prognosis, mainly by regulating the response of TNBC to the chemotherapy drug doxorubicin. The high expression of miR-449a was significantly associated with a good prognosis by Metabric study-GEO database, while miR-449b/c was not associated with prognosis [186]. Tsiakou et al analyzed the single nucleotide polymorphisms (SNPs) of miR-34, and the result showed that the TNBC patients with TC/CC genotype in the rs4938723 C>T polymorphism had shorter OS intervals with worse prognosis [187].…”
Section: Prognostic Implications Of Mirnas In Tnbcmentioning
confidence: 99%